2005
DOI: 10.1083/jcb.200409182
|View full text |Cite
|
Sign up to set email alerts
|

Sox2 induction by FGF and FGFR2 activating mutations inhibits Wnt signaling and osteoblast differentiation

Abstract: Activating mutations in fibroblast growth factor receptor 2 (FGFR2) cause several craniosynostosis syndromes by affecting the proliferation and differentiation of osteoblasts, which form the calvarial bones. Osteoblasts respond to FGF with increased proliferation and inhibition of differentiation. We analyzed the gene expression profiles of osteoblasts expressing FGFR2 activating mutations (C342Y or S252W) and found a striking down-regulation of the expression of many Wnt target genes and a concomitant inducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
215
1
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(238 citation statements)
references
References 54 publications
15
215
1
7
Order By: Relevance
“…Previous studies reported conflicting results on the role of FGFR2 in the control of osteoblast differentiation. Genetic manipulation in murine osteoblasts indicated that gain-of-function mutations of FGFR2 can either reduce (51,54) or increase osteoblast differentiation (55)(56)(57)(58). The present data provide novel evidence for a positive role of activated FGFR2 on osteogenic differentiation of murine mesenchymal cells in vitro.…”
Section: Discussionsupporting
confidence: 49%
“…Previous studies reported conflicting results on the role of FGFR2 in the control of osteoblast differentiation. Genetic manipulation in murine osteoblasts indicated that gain-of-function mutations of FGFR2 can either reduce (51,54) or increase osteoblast differentiation (55)(56)(57)(58). The present data provide novel evidence for a positive role of activated FGFR2 on osteogenic differentiation of murine mesenchymal cells in vitro.…”
Section: Discussionsupporting
confidence: 49%
“…Downregulation of the cyclin D1 mRNA and upregulation of the p27 Kip1 mRNA were also observed after SOX2 overexpression (data not shown), indicating that these cell-cycle-regulating factors may be controlled by SOX2 at the transcriptional levels. It has been reported that b-catenin activates the transcription of cyclin D1 through TCF-binding sites within the promoter, resulting in a direct effect on cell proliferation in colon carcinoma cells (Tetsu and McCormick, 1999), whereas SOX2 associates with b-catenin in osteoblasts and inhibits the activity of a Wnt-responsive reporter plasmid in HEK293 cells (Mansukhani et al, 2005). It is, thus, possible that SOX2 may function in the cell cycle through interaction with Wnt signals in gastric epithelial cells.…”
Section: Roles Of Sox2 In Gastric Carcinogenesismentioning
confidence: 99%
“…Importantly, the Wnt/β-catenin pathway is active in the early developing ovary and inactive in the early developing testis (Chassot et al, 2008). Furthermore, a number of SOX proteins, such as SOX1, SOX2, SOX3, SOX7, SOX9 and SOX17 inhibit the canonical Wnt/β-catenin signaling in different models of chondrocyte, neuronal and intestinal differentiation; however the mechanism of their action is still unclear (Akiyama et al, 2004, Bastide et al, 2007, Kan et al, 2004, Mansukhani et al, 2005, Sinner et al, 2007, Takash et al, 2001, Zorn et al, 1999. Here we investigated whether SRY could inhibit the canonical Wnt/β-catenin pathway.…”
Section: Introductionmentioning
confidence: 99%